Validation of the Persian Version of the National Institute of Health Chronic Prostatitis Symptom Index - Allameh, Farzad; Mansouri Tehrani, Mohammad Mersad; Tasharrofi, Mohammad Ali; Ganji Jameshouran, Mohammad Ali (Urology Journal, 2020)
Objectives: To compose a comprehensible and fluent Persian translation of the National Institute of Health Chronic Prostatitis Symptom Index (NIH-CPSI), and to determine its linguistic validity in a Persian sample population. Methods: The standard double-back translation method, provided by the previous studies were utilized by three professional linguists to translate the English version of the NIH-CPSI to Persian, and a group of 10 urologists further reviewed and translated questionnaire. The questionnaire was then presented to the sample study, comprised of 60 men with CP/CPPS and 60 controls with adverse urological history, and the collected data was analyzed through IBM-SPSS software to test its validity, evaluative, and discriminatory power, psychometric qualities and internal consistency. Results: A total of 80 subjects (42 CP/CPPS patients and 38 healthy controls) were considered eligible for this study. The total Persian NIH-CPSI scores and each subdomain showed significant difference (P < 0.001) between the two study groups, indicating a satisfactory discriminant validity for the index. Psychometric analysis established the index to benefit from a high internal consistency. The translation was also considered by both the subjects and the physicians to be easily comprehensible. Conclusion: The Persian NIH-CPSI is a reliable and valid instrument for evaluating CP/CPPS symptoms in general population, while also benefitting from high discriminatory power, and can be utilized with ease in both clinical practice and laboratory studies.